2018
DOI: 10.12659/msm.909254
|View full text |Cite
|
Sign up to set email alerts
|

High Interleukin-37 (IL-37) Expression and Increased Mucin-Domain Containing-3 (TIM-3) on Peripheral T Cells in Patients with Rheumatoid Arthritis

Abstract: BackgroundAnti-inflammatory mediators such as mucin-domain containing-3 (TIM-3) and IL-37 play an important role in the regulation of Th1-mediated immunity. This study was designed to investigate the proportions of various T cell subsets and monocytes in the peripheral blood of rheumatoid arthritis (RA) patients, as well as the level of TIM-3 on these cells and serum cytokine levels.Material/MethodsWe enrolled 59 RA patients and 46 age- and sex-matched healthy controls in this study. The proportion of T cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Elevated expression of IL‐37 was positively correlated with disease activity index. These findings are in agreement with previous studies . In recent years, increasing evidence has shown that IL‐37 is implicated in rheumatic autoimmune diseases.…”
Section: Discussionsupporting
confidence: 93%
“…Elevated expression of IL‐37 was positively correlated with disease activity index. These findings are in agreement with previous studies . In recent years, increasing evidence has shown that IL‐37 is implicated in rheumatic autoimmune diseases.…”
Section: Discussionsupporting
confidence: 93%
“…In our previous report, serum Gal–9 and sTIM–3 were significantly elevated in RA patients compared with healthy subjects [ 21 , 22 ]. A relationship between proinflammatory cytokines and Gal–9/TIM–3 has been reported in RA patients [ 23 , 24 ], so we hypothesized that immune–checkpoint molecules are possible modulators of immunopathology in RA through their interactions with cytokines. In this study we investigated the influence of these combined biomarkers, including autoantibodies, cytokines, and immune-checkpoint molecules, on the disease activity of RA.…”
Section: Introductionmentioning
confidence: 99%
“…After that, the publications continued to rise in IL-37 research, which implies that IL-37 has also gained much attention. Increased levels of circulating IL-37 have been reported in the patients with rheumatoid arthritis (37,(44)(45)(46)(47)(48), multiple sclerosis (49)(50)(51), and systemic lupus erythematosus (12,(52)(53)(54). Patients with rheumatoid arthritis demonstrated an increased level of synovial IL-1R8, which is essential for the antiinflammatory effects of IL-37.…”
Section: Discussionmentioning
confidence: 99%